Converging and diverging stances on target varieties in collateral languages: The ideologies of linguistic variation in Irish and Manx Gaelic - O Murchadha, Noel (My University, 2018)
This article will argue that language revival movements, particularly those founded in the ethno-nationalist era of the late 19thand early 20thcenturies, retain founding overt beliefs rooted in an ideological commitment to a specific language because of its role as the authentic and legitimate cultural vehicle of a distinct people. Revival is thus the reinstatement of cultural distinctiveness based on traditional language. Revivalists have in the past afforded the language varieties of the remaining traditional native speech communities a high prestige status based on their perceived ethnolinguistic authenticity. However, after more than a century of language maintenance and revivalism, significant linguistic institutionalisation, a strong presence in schooling and new socialisation mechanisms outwith the traditional speech communities,some minoritised languages have regained a degree of their sociolinguistic vitality by the advent of ‘new speakers’ who have no organic relationship with the traditional language community. The ways that these ‘new speakers' and ‘learners' of previously displaced languages negotiate linguistic authenticity and ethno-cultural legitimacy in our contemporary late modern period provide challenges to established value-laden perceptions about language revitalisation and regeneration of traditional speech communities and the long-held belief in the prestige of ‘native’ speech as the target variety. This discussion will draw on data from recent fieldwork among contemporary speakers of Irish and Manx Gaelic in order to analyse both their overt and more hidden beliefs about the utility and legitimacy of traditional and revival speech. It will further argue that ‘traditional’ and ‘new’ speakers do not live parallel sociolinguistic realities in which they are sociolinguistically isolated from one another, but rather that contemporary speakers contest the prestige of both traditional and innovative revival varieties in their language practices and ideologies in a multi-faceted fashion.
PUBLISHED
Keywords: Language ideology; Folk linguistics; Linguistic variation; Irish; Manx Gaelic; Identities in Transformation; Applied Linguistics; Celtic Linguistics; Folk Linguistics; LINGUISTICS; SOCIOLINGUISTICS